Penerapan Pendekatan Pembelajaran TERPADU pada Sekolah Dasar Islam Terpadu (SDIT) - Eni Triani Yuliana; Sunarti Sunarti (Proceedings Series on Social Sciences & Humanities, 2022)
TERPADU learning approach is an abbreviation of the learning stages, namely Telaah, Eksplorasi, Rumuskan, Presentasikan, Aplikasikan, Duniawi, Ukhrowi, all are implemented as learning activities in the classroom. This approach was developed by JaringanSekolah Islam Terpadu (JSIT) to be implemented by all Integrated Islamic Schools under its auspices. However, in reality, not all schools understand and apply this approach. This study aims to determine how the application of the INTEGRATED learning approach in the Integrated Islamic Elementary School. The methodology used in this research is a combined method (mix method), which is a research method that combines quantitative methods and qualitative methods to be used together in the research activity, so that more comprehensive, valid, reliable, and reliable data are obtained and objective. Researchers carried out observations and documentation of the lesson plans and how to teach teachers in the classroom, distributed questionnaires to teachers, and conducted interviews with the Principal at the Integrated Islamic Elementary School or Sekolah Dasar Islam Terpadu (SDIT). This study concludes that most teachers at SDIT have implemented an INTEGRATED learning approach in teaching and learning activities in the classroom. Principals and Curriculum have encouraged teachers to create INTEGRATED learning designs to be applied to classroom learning. The school provides full support for the implementation of the INTEGRATED learning approach in the classroom by providing the various facilities needed. Students actively participate in learning in class and complete assignments well.